Hubungan Pengetahuan Remaja Dan Peran Teman Sebaya Terhadap Perilaku Pencegahan Kehamilan Pada Usia Remaja Di Sman 02 Seluma Tahun 2025 - Rika Rika; Danur Azissah; Nuche Marlianto (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The phenomenon of teenage pregnancy remains a significant reproductive health issue, both globally and nationally. Based on WHO data and national reports, Indonesia still has a high teenage birth rate. This study aims to determine the relationship between knowledge and the role of peers in preventive behaviour against teenage pregnancy at SMAN 02 Seluma. The method used in this study is a quantitative approach with a cross-sectional method. The research sample consisted of 79 female students in grades X and XI, selected using purposive sampling. Data collection was conducted using a closed questionnaire that had been tested for validity and reliability. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test. Based on the results of the univariate analysis, the study showed that most respondents (47 or 59.5%) had a low level of knowledge, most respondents (44 or 55.7%) had a negative peer role, and most respondents (46 or 58.2%) had negative pregnancy prevention behaviour. Bivariate analysis of normality tests found a relationship between adolescent knowledge and pregnancy prevention behaviour among adolescents at SMAN 02 Seluma in 2025, as seen using the Chi-Square test (Person Chy-Square), which yielded a value of 6.981 with a p-value of 0.030 (< 0.05). There was a relationship between the role of peers and pregnancy prevention behaviour among adolescents at SMAN 02 Seluma in 2025, as seen using the Chi-Square test (Continuity Correction), which yielded a value of 5.022 with a p-value of 0.025 (< 0.05). It was concluded that both knowledge and the role of peers influenced pregnancy prevention behaviour among adolescents. It is hoped that schools and health workers can improve education and form positive peer groups to reduce the number of teenage pregnancies.